X-ray micro-computed tomography and ultrasonic velocity analysis of fractured shale as a function of effective stress. (December 2019) - Yu, Hongyan; Zhang, Yihuai; Lebedev, Maxim; Wang, Zhenliang; Li, Xiaolong; Squelch, Andrew; Verrall, Michael; Iglauer, Stefan
Abstract: Ultrasonic velocity is a key shale gas reservoir property, especially in the context of gas production or CO2 injection for geo-sequestration. This ultrasonic velocity reflects the dynamic elastic properties of the rock, and it thus depends on the fracture morphology, which varies significantly with effective stress. However, the precise relationship between ultrasonic velocity and fractured shale morphology is only poorly understood. We thus measured P- and S-wave velocities of fractured shale in two orthogonal directions and imaged the shale with X-ray micro-computed tomography as a function of applied effective stress; and investigated how fracture morphology, P- and S-wave velocity, Young's modulus, shear velocity and Poisson's ratio are interconnected with effective stress. Clearly, most of the small fractures (the width is around 0.1 mm) closed with increasing effective stress, resulting in a different fracture size distribution, which again had a dramatic effect on the elastic rock properties. Furthermore, with increasing effective stress, P- and S-wave velocities increased significantly, such that the orthogonal waves gave a similar response at 2000 psi effective stress despite significant sample heterogeneity. We conclude that the fracture aperture, direction and network characteristics severely influence wave propagation and thus elastic properties. These results can be used to assess natural fracture networks, monitor fracture development during hydraulic fracturing, and predict fracture closure scenarios during production. Highlights: Small fractures closed with increasing effective stress. With increasing effective stress, P- and S-wave velocities increased significantly. The fracture aperture, direction and network characteristics severely influence wave propagation and thus elastic properties.